Correlation of Serum Chromogranin A with HbA1c and eGFR in Different Groups of Type 2 Diabetic patients - Amna Ghaffar, Huma Hussain, Nida Khaliq, Iffat Norren, Ammar Ahmad, Syed Sufyan Khaliq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: World health organization estimated that around 422 million people are living with diabetes and there is an increasing trend in the number of diabetic patients. Aim: To correlate the levels of serum chromogranin A with HbA1c and eGFR in different groups of type 2 diabetic patients based on urinary Albumin- Creatinine Ratio. Methodology: This cross sectional comparative study was done by enrolling 116 patients at Chemical Pathology Department, LGH-Lahore through probability convenient sampling. Urine samples of all subjects were centrifuged in-order to measure urinary albumin and creatinine. Laboratory parameters like Urinary albumin, Serum creatinine and HbA1c were measured. HbA1c was measured using HPLC method. Serum creatinine was measured kits on fully automated spectrophotometer. Abbreviated MDRD equation calculated eGFR. Data SPSS v.24 analyzed the data. ANOVA test applied with P-value of less than 0.05 was considered significant. Spearman correlation was also applied to correlate HbA1c and eGFR with CgA in each group. Results: The results showed that eGFR was normally distributed whereas, the distribution of albumin creatinine ratio, HbA1c, serum creatinine and serum chromogranin-A were not normal. Between the A, B, and C groups, no discernible variation in the mean HbA1c values was found. Practical Implication: Due to lack of literature review and high incidence of diabetes induced nephropathy in our setups, there is need to find a parameter than can correlate nephropathy among diabetics. Conclusion: It was concluded that early diagnosis of diabetic nephro-pathy can be evaluated by using serum Chromogranin-A but it has a negative correlation with eGFR and positive correlation with HbA1c. Keywords: Diabetic Nephropathy, HbA1c, Estimated Glomerular Filtration Rate, Serum Chromogranin-A and Type-2 Diabetes.